Recent Progress in the in situ Detrifluoroacetylative Generation of Fluoro Enolates and Their Reactions with Electrophiles - Mei, Haibo; Xie, Chen; Aceña, José Luis; Soloshonok, Vadim A.; Röschenthaler, Gerd-Volker; Han, Jianlin (European journal of organic chemistry, 2015)
Detrifluoroacetylative generation of fluoro enolates is an emerging area of high‐impact research. In this review article we provide, for the first time, a comprehensive and critical treatment of this subject. The reaction types reported to date include Mannich, aldol, and Michael addition and halogenation reactions. These processes can be very successfully conducted in asymmetric fashion, in stoichiometric or catalytic mode. In general, these reactions allow for synthetically rather simple and practical installation of CF2, CHF, and quaternary CF structural units into various types of organic compounds. In particular, the overall scientific importance, as well as the potential influence of this methodology for the development of useful approaches to the preparation of pharmaceutically valuable compounds is highlighted. Attractive features such as operationally convenient, mild reaction conditions, remarkable substrate generality, and excellent stereochemical outcome bode well for widespread applications of this innovative and synthetically advanced approach. The high‐impact research in the new emerging area of detrifluoroacetylative in situ generation of fluoro enolates is comprehensively presented. The major reaction types featuring in this process include Mannich, aldol, and Michael addition and halogenation reactions. The scientific importance and practical potential of this methodology is highlighted and critically discussed.